Event-Triggered Change Control for Production Inventory Systems With Average Dwell Time - Gao, Xue-Feng; Fan, Jia-Hui; Liu, Wei; Li, Qing-Kui; Peng, Chen (Chinese Control Conference, 2021)
This paper studies change control based on the event-triggered scheme for production inventory systems with average dwell time and time-varying delays. By considering the stock levels of different warehouses, a switching time-varying delay system is introduced to model the production inventory systems, which is consisted of two facilities with different review periods. Change control is designed to tackle the problem of system parameters varying during the system evolving with unexpected emergencies. The event-triggered scheme is used to determine the transmission of raw materials (or finished products), which is more appropriate than the period transmission in practice, and switching among subsystems is satisfied with the conditions of average dwell time. Sufficient conditions of exponentially stable and controller existence are derived by the switching control theory and the Lyapunov-Krasovskii theory. The bullwhip effect, which is resulted by uncertain customers' demand, is attenuated by H ∞ control method. A potassium carbonate production inventory system is given as an example to illustrate the effectiveness of the proposed methods.